A113: TCR‐independent Activation of T‐cells Through CD31 Triggering as an Etiology of Cytokine Production in Juvenile Idiopathic Arthritis. Issue 11 (March 2014) - Ferguson, Ian D.; Griffin, Patricia; Michel, Joshua; Kietz, Daniel; Rosenkranz, Margalit; Vallejo, Abbe N.
Abstract : Background/Purpose: JIA is the banner diagnosis for a heterogenous group of rheumatic conditions characterized by local inflammation and destruction of the joint space and systemic manifestations. Pro‐inflammatory cytokines derived from T cells are considered effectors of disease. Recent data has shown that some of these cytokines come directly from a distinct subset of T cells expressing CD31, an adhesion molecule expressed by granulocytes and endothelial cells. In the present work, we examined whether the array of cytokines in blood and synovial fluid of patients are the same array produced by T cells activation through CD31 ligation independent of the TCR. We propose that CD31‐driven cytokine production by T cells is a self‐perpetuating mechanism of local and systemic inflammation in JIA. Methods: Following informed consent/assent, blood and/or synovial fluid were collected from patients with oligoarticular and polyarticular JIA. Similar blood samples were also collected from healthy subjects. Cytokine composition of the plasma and/or fluid were subjected to multiplex analysis using the Luminex platform. Phenotypes of mononuclear cells in blood and synovial fluid were examined by multicolor flow cytometry. Drawing from the results of the Luminex assay, receptor crosslinking bioassays using primary CD31+ T cells (in blood and/or synovial fluid) and CD31+ T cell lines were conducted. Cytokine production by these cells were assessed by flow cytometry and/or by Luminex. Results: The overall cytokine signature of JIA characterized by the dominance of IL‐6, IL‐10 and TNFα. Unexpectedly, patients with oligoarticular disease showed higher levels of IFNγ and IL‐17 family cytokines than those with polyarticular disease. Both types of patients however showed a similar cellular signature characterized by the preponderance of T cells deficient in CD4, CD8, and CD28, but expressing CD31. Results of CD31 cross‐linking bioassays, using either specific antibody or its recombinant ligand CD38, showed high levels of induction of IL‐2, IL‐17 and IFNγ. Specificity of CD31‐driven, TCR‐dependent cytokine production was verified by similar bioassays using somatic somatic T cell line mutants Loucy and JRT3 that lack TCR and TCR/CD3, respectively, but are both CD31+. The observed cytokine production was associated with the phosphorylation of the signaling substrates ZAP70, cAbl, and p65‐NFKB. Conclusion: Our data show that the cytokine signature of oligoarticular JIA appears distinct with the dominance of IFNγ and IL17. TCR independent, CD31‐driven induction of these cytokines suggests maladaptive T cell function in JIA. Further investigation on the relevance of IFNγ and IL‐17 to disease activity/clinical outcomes, and the CD31 signaling pathway will pave way to innovations in immunotherapy in JIA.